Variability in coastal habitat available for Longfin Smelt Spirinchus thaleichthys in the northeastern Pacific Ocean - Matthew J. Young; Frederick V. Feyrer; Steven T. Lindley; David D. Huff (Frontiers in Marine Science, 2024)
An understanding of oceanographic conditions and processes important to marine animal ecology is fundamental to the development of effective management and conservation actions. Longfin Smelt ( Spirinchus thaleichthys ) is a pelagic forage fish found in coastal and estuarine waters along the Pacific coast of North America from Alaska to central California. Substantial population declines in California’s San Francisco Estuary, where Longfin Smelt are protected under California’s Endangered Species Act, have prompted extensive study of estuarine factors associated with the decline. However, coastal factors that affect up to two-thirds of the Longfin Smelt life cycle are poorly understood and may be important drivers of population dynamics. We compiled coastal observations from numerous sources to estimate the range-wide coastal marine distribution of Longfin Smelt and assess habitat factors affecting distribution in the northeast Pacific Ocean. Based on maximum entropy species distribution models, Longfin Smelt distribution was correlated with depth, distance from the nearest estuary, sea surface temperature, and sea surface chlorophyll. Longfin Smelt were found in shallow, higher productivity coastal waters closer to estuaries, with depth and temperature the most consistent factors influencing distribution. Habitat suitability was highly variable at the southern extent of the range, particularly off the California coast, and was largely driven by habitat contractions associated with warm-water conditions. Study results provide insights into the habitat and range-wide distribution of an at-risk estuarine-reliant forage fish and are the first step toward identifying processes that affect the marine portion of the Longfin Smelt life cycle.

Matrix metalloproteinase- 9 may contribute to collagen structure modification during postmortem aging of beef - Larissa A. Koulicoff; Terra Heilman; Lauren Vitanza; Amelia Welter; Haley Jeneske; Travis G. O'Quinn; Stephanie Hansen; Elisabeth Huff-Lonergan; Matthew D. Schulte; Michael D. Chao (Meat Science, 2023)

PanoMRT: Panoramic infrared thermography to model human thermal exposure and comfort - Ariane Middel; Matthew Huff; E. Scott Krayenhoff; Ananth Udupa; Florian A. Schneider (Science of The Total Environment, 2023)

Chloroplast genome of the invasive Pyrus calleryana underscores the high molecular diversity of the species - Marcin Nowicki; Matthew L. Huff; Margaret E. Staton; Robert N. Trigiano (Journal of Applied Genetics, 2022)
The complete chloroplast genome of Pyrus calleryana (GenBank OM541581.1) was developed by de novo assembly from whole-genome sequencing data. Reference-guided ( P. phaeocarpa ) read mapping and assembly were followed by annotation and phylogenetic comparisons. The 159,965 bp P. calleryana chloroplast genome represented 36.56% GC content with a classical quadripartite architecture and two inverted repeats regions (IRs; each 26,392 bp) separating the large single-copy region (LSC; 87,942 bp) and the small single-copy region (SSC; 19.239 bp). In total, 125 unique features were annotated in that genome, including 83 protein coding genes, 38 tRNA coding genes, and 4 rRNA coding genes. Phylogenetic analyses based on the whole chloroplast genome sequences placed the P. calleryana among other Rosaceae plants, specifically among the Asian species of Pyrus .

“A reference genome assembly and adaptive trait analysis of Castanea mollissima ‘Vanuxem,’ a source of resistance to chestnut blight in restoration breeding” - Margaret Staton; Charles Addo-Quaye; Nathaniel Cannon; Jiali Yu; Tetyana Zhebentyayeva; Matthew Huff; Nurul Islam-Faridi; Shenghua Fan; Laura L. Georgi; C. Dana Nelson; Emily Bellis; Sara Fitzsimmons; et al. (Tree Genetics & Genomes, 2020)

Good Practices for Species Distribution Modeling of Deep-Sea Corals and Sponges for Resource Management: Data Collection, Analysis, Validation, and Communication - Arliss J. Winship; James T. Thorson; M. Elizabeth Clarke; Heather M. Coleman; Bryan Costa; Samuel E. Georgian; David Gillett; Arnaud Grüss; Mark J. Henderson; Thomas F. Hourigan; David D. Huff; Nissa Kreidler; et al. (Frontiers in Marine Science, 2020)